Disability and teaching - Gabel, Susan L. (Susan Lynn), 1956-; Connor, D. J. (New York : Routledge, 2014)
This work highlights issues of disability in K-12 schooling faced by teachers, who are increasingly accountable for the achievement of all students regardless of the labels assigned to them. It is designed to engage prospective and practicing teachers in examining their personal theories and beliefs about disability and education. Part one offers four case studies dealing with issues such as inclusion, over-representation in special education, teacher assumptions and biases, and the struggles of novice teachers. These cases illustrate the need to understand disability and teaching within the contexts of school, community, and the broader society and in relation to other contemporary issues facing teachers. Each is followed by space for readers' reactions to the educators' dialogue, a summary, and additional questions. Part two presents public arguments representing different views about the topic: conservative, liberal-progressive, and disability centered. Part three situates the authors' personal views within the growing field of disability studies in eduation and provides exercises for further reflection. -- From back cover.
Case Studies and Reactions. Case 1:'Inclusion Tension' ; Reader reactions to'inclusion tension' ; Reactions to'inclusion tension' ; Reader reactions. -- Case 2:'Ableism at Forest Run Elementary' ; Reader reactions to'ableism at Forest Run Elementary' ; Reactions to'ableism at Forest Run Elementary' ; Reader reactions. -- Case 3:'Race, Place, and the Search for Solutions' ; Reader reactions to'Race, place, and the search for solutions' ; Reactions to'race, place, and the search for solutions' ; Reader reactions. -- Case 4:'Martin Louis, Special Educator?' ; Reader reactions to'Martin Louis, special educator?' ; Reactions to'Martin Louis, special educator?' ; Reader reactions ; Reader reactions to the four cases ; Reactions to the four cases. -- Public Arguments. A'conservative view' : rewarding achievement, maintaining tradition ; A'liberal-progressive view' : celebrating diversity, creating equity ; A'disability-centered view' : acknowledging difference, deconstructing normalcy. -- A Final Argument., and Some Suggestions and Resources for Further Reflection. Disability, teaching, and schools: an abbreviated view ; The permanence of ableism and necessary action ; Our educational strategies ; Exercises for further reflection ; Recommendations -- Personal narratives -- Useful websites.
Includes bibliographical references and index.
Keywords: People with disabilities -- Education -- Case studies